2019
DOI: 10.1093/jbcr/irz058
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Early Use of an End of Range Axilla Orthotic in Children Following Burn Injury

Abstract: Scar contracture is a significant complication of burn injury. This study aimed to describe outcomes of early axilla orthotic use at end of range abduction in children, following a burn to the axilla region. A retrospective review of 76 children (mean age 3.9 years [SD 3.6]) treated at a tertiary children’s hospital from 2006 to 2016 was conducted. No child developed axilla contracture for the duration of the 2-year study follow-up with no adverse events recorded. If orthotic use was ceased <60 days post-bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Consequently, these children represented a large percentage of the HTS groups at both time points post burn. Prior research reports HTS prevalence rates for all children post burn injury as 16%–69%, 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 and for children treated conservatively as 10.4%–41.0%. 3 , 5 , 6 , 8 , 14 Similarly, the current study found the prevalence of HTS to be 56.1% at 3–6 months, and 16.3% at 12–18 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, these children represented a large percentage of the HTS groups at both time points post burn. Prior research reports HTS prevalence rates for all children post burn injury as 16%–69%, 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 and for children treated conservatively as 10.4%–41.0%. 3 , 5 , 6 , 8 , 14 Similarly, the current study found the prevalence of HTS to be 56.1% at 3–6 months, and 16.3% at 12–18 months.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 This wide range stems from varied study populations, the use of multiple measurement tools and varied values in the subjective scar scales used to determine the presence or definition of HTS. 15 Differing follow‐up durations during the scar development and maturation phases, ranging from 1 week to 5 years, 3 , 5 , 6 , 8 , 9 , 10 , 14 further compounds the variability of HTS prevalence within the literature. The lack of a formal scar definition within the burn community challenges researchers and clinicians abilities to compare outcomes and incidences of HTS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shoulder is mobile anteriorly, posteriorly, and laterally, needing a full skin mobility in all aspects of the region. A large range of functional deficits may be encountered in burns, with a good reactivity to early physiotherapy and specifically to range axilla orthotic, as demonstrated [3] (. Figs.…”
Section: Axillar Contracturesmentioning
confidence: 99%
“…Recent studies have highlighted the effectiveness of stretching in enhancing the range of motion, particularly in flexion and abduction among upper limb burn patients, thereby reducing the incidence of axillary contracture (4,14,15). Conversely, other research emphasizes the benefits of positioning patients in airplane splints to provide abduction support, which not only improves the range of motion in the shoulder but also enhances patient mobility and functional status (5,16,17). This comparative analysis aims to elucidate the relative impacts of stretching and splinting in improving shoulder range of motion in post-burn axillary contracture patients, with the ultimate goal of decreasing the development of contracture and enhancing the recovery rate and functional status of these individuals.…”
Section: Introductionmentioning
confidence: 99%